Macromarketing--a global focus : marketing systems, societal development, equity & poverty (vol.1-4) - Shapiro, Stanley J.; Tadajewski, Mark.; Shultz, Clifford J. (Los Angeles : SAGE, 2009)
Includes bibliographical references